A conceptual model for understanding the process of self-leadership development and action-steps to promote personal leadership development. Issue 4 (8th April 2014) - Ross, Stanley
Abstract : Purpose: – The goal of the leadership development process is to enable the individual to learn how to become a self-leader and for any organization to develop leaders. Self-leadership represents an individual's ability to exercise control (self-efficacy) over his or her choice of situations in which to participate in and to provide intrinsic rewards that are usually associated with achieving goals. The paper aims to discuss these issues. Design/methodology/approach: – This study presents and describes a conceptual model that will help us to understand the critical dimensions (e.g. self-esteem) associated with self-leadership and the interrelatedness of these dimensions. Findings: – The conceptual model that the author describes in this paper provides a comprehensive overview of self-leadership that extends Neck and Manz's (2010) conceptual model. It does so by identifying all the critical super ordinate mediators referred to by Deci et al. (1981) as internal states (referred to in this study as "dimensions"). These "dimensions" are then organized into his or her own singular system which leads to specific types of behavior. Through elucidating the important mediators and learning about and understanding how behavior, an individual's internal processes and external forces influence each other (in what Manz, 1986; Bandura, 1978 refer to as reciprocal determinism), we can begin to understand how to design more effective leadership development programs. Additionally, by studying these mediators any organization can develop clearly defined profiles of potential leaders; in turn, this will help an organization screen candidates more effectively to fill leadership jobs. Originality/value: – This concept piece offers a comprehensive model of the self-leadership process that includes all the important issues and the relationship among the important issues.